Pengaruh Implementasi Kebijakan Pemeriksaan dan Forensik Digital terhadap Kualitas Pemeriksaan dan Keberhasilan Penerimaan Pajak - Dian Shavitri, Luh Putu; Sri Darma, Gede (E-Jurnal Akuntansi, 2020)
This study aims to obtain empirical evidence on the influence of the implementation to determine the priority of Taxpayer to be audited policy, access to financial information for tax purposes policy and digital forensics toward tax audit quality and tax revenue in Bali Regional Office of Directorate General of Taxes. The approach that is used is quantitative approach using purposive sampling method in determining sample and Partial Least Square (PLS) method as data analysis technique. This study revealed that the implementation to determine the priority of Taxpayer to be audited policy, access to financial information for tax purposes policy and digital forensics has a positive and significant effect toward tax audit quality and tax revenue collection. Indonesia's tax ratio is still relatively low. Keywords: Taxpayer Audit Priority; Bank Account Opening; Digital Forensics; Tax Audit Quality, Tax Revenue.